2000
DOI: 10.1038/sj.ijo.0801202
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in perceptions of body size in middle-aged European, Maori and Pacific People living in New Zealand

Abstract: OBJECTIVES: The aim of this study was to compare perceptions of body size in European, Maori and Paci®c Islands people with measured body mass index (BMI), waist-to-hip ratio and change in BMI since age 21 y. Socio-demographic factors that in¯uenced perceptions of body size were also investigated. DESIGN: Cross-sectional survey. METHODS: Participants were 5554 workers, aged ! 40 y, recruited from companies in New Zealand during 1988 ± 1990. RESULTS: Prevalences of BMI b 25 kgam 2 were: Europeans, 64.7% men, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
53
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 23 publications
9
53
1
Order By: Relevance
“…Most previous studies in New Zealand have only sampled adult Europeans (Birkbeck, 1979;Scragg et al, 1991), although a recent national survey reported frequencies of consumption of various foods in Maori and non-Maori adults, and reported median nutrient intakes by gender and ethnicity (Russell et al, 1999). Only one other study has compared the food and nutrient intakes of Pacific adults with Maori and Europeans in New Zealand (Metcalf et al, 1998), and Ferguson et al (1995) examined these ethnic differences for intakes of plant foods in this population. Bell et al (1999) examined the dietary intakes of adult Samoans from New Zealand church communities.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies in New Zealand have only sampled adult Europeans (Birkbeck, 1979;Scragg et al, 1991), although a recent national survey reported frequencies of consumption of various foods in Maori and non-Maori adults, and reported median nutrient intakes by gender and ethnicity (Russell et al, 1999). Only one other study has compared the food and nutrient intakes of Pacific adults with Maori and Europeans in New Zealand (Metcalf et al, 1998), and Ferguson et al (1995) examined these ethnic differences for intakes of plant foods in this population. Bell et al (1999) examined the dietary intakes of adult Samoans from New Zealand church communities.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In Western societies, thinness is associated with self-control, elegance, youthfulness and attractiveness, and women of higher socioeconomic groups are less likely to be obese. 9 The situation in some developing countries appears to be the opposite, and some authors 12,14,15 conclude that obesity is admired and seen as sexually desirable, and a symbol of social success and wealth in countries where economic resources are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing ethnic differences in perception of body size have contrasted Caucasian women with Polynesians, 20 Afro-Americans 21 and Maori/Tongans. 9 All these studies have clearly shown that Caucasian women prefer slimmer body sizes, they often overestimate their current body size, their cultural ideal is thinness and more are dissatisfied with their body size compared with women from the other ethnic groups investigated. Although studies in Afro-Americans largely follow this trend, there is recent evidence that this may be changing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] There is a lot of data on the prevalence rates of obesity in the general population in Bahrain and other Arabian Peninsula states, [10][11][12] where the prevalence rate among adults is among the highest in the world. 13,14 Diabetes rates are increasing even more quickly in Arab countries.…”
mentioning
confidence: 99%